Haze problems in Samoeng district Chiang-mai, Thailand - Teeputai Saengas; Thanarin Harnkiattiwong (EQA)
The weather around the world is changing. Its quality is deteriorating due to contamination from toxic substances, which may be in various forms such as gases and dust, which is called air pollution. This is a problem that the worldwide is concerned because it affects human health and causes serious diseases. The upper northern region of Thailand has been facing this problem for a long time, more than 2 decades. Therefore, this research aims to investigates the cause and find ways to solve the problem using qualitative research, physical and environmental survey techniques of the community, observation, in-depth interviews 34 key informants, data collection period from January to December 2024. The research results found that: the cause of the haze in Samoeng District is open burning and forest fires, which are caused by hunting and foraging forest products, which are the way of life of the people in this area. The factors that promote the severity of the haze problem are winds blowing across the border from other areas, climate change, and the basin. The short-term or urgent solution is, watering the roadsides to create a wet firebreak to prevent forest fires. The development of drones to better quality for extinguishing fires. The long-term solution is to strictly enforce the law against those who create sources of haze. The development of technology and modern tools can identify the source and amount of pollution. The last approach is to join in solving the haze problem at the regional and global level to benefit from technology transfer from countries with the potential to solve the problem.